Online Marketing that Humanism on E-commerce - Christanto Edy, Irwan; Marsono, Shandy; Sri Haryanti, Setyani (International Journal of Engineering and Technology, 2019)
Humanism is an understanding that emphasizes dignity, ethics, which upholds human values. Humanism is related to human life including business. The purpose of this study is to examine the contribution model of humanism to online shopping decisions. This study uses a population that is a group of employees belonging to the millennial generation in the city of Surakarta Indonesia. The research uses the surve method. Instrument for collecting data with a questionnaire. The number of respondents obtained is 100 people. Convenience Sampling data collection techniques, namely the method of collecting samples based on the availability of elements and the ease of obtaining them. Samples are taken or selected because the sample is in the right place and time. Humanism indicators include the values of honesty, openness, justice, religious and social community. Testing instruments using validity and reliability. Statistical analysis with SEM (Sequential Equation Model) because of the assumption that the amount of data is normally distributed. The results showed that 1) humanism had a positive but not significant effect on online promotion through e-commerce websites, 2) humanism had a negative and not significant effect on online shopping decisions, 3) online promotion through e-commerce websites had a positive and significant effect on online shopping decisions.Â